A Institucionalização das Ações Afirmativas Estudantis na Universidade Estadual do Piauí (UESPI): avanços a conta-gotas - Nóbrega, Evangelita Carvalho da (2024)
The institutionalization of affirmative action policies in higher education in Brazil, in the form of access, has been taking place since 2002, based on the autonomy of universities, in state and/or federal legislation. It should be noted that the democratization of access requires transformation in higher education institutions. The challenge now is to institutionalize the policy of student permanence, as it is a phenomenon that is emerging and expanding, and can lead to the construction of a new model of university, plural, diverse, popular, anti-racist, democratic, with indicative affirmative action becoming effective and full. However, the public resources made available by the state for affirmative action are insufficient to guarantee the rights of students in situations of socio-economic vulnerability and inequality. Given that it is the responsibility of the HEIs to institutionalize affirmative action for students, these actions occur in a variety of ways, as they require organizational tools for administrative, pedagogical and academic management. In this sense, the general objective of this research was to understand the institutionalization of affirmative student actions, materialized in the normative instruments, which imply the development of the policy of access and permanence for quota students at UESPI. We opted for bibliographical and documentary research, with a qualitative approach. The investigation was supported by legal frameworks, legislation, theoretical approaches and reflections on historical contexts that deal with educational policies, in the dimension of affirmative student actions. Documentary analysis based on Bardin (1977). The data analysis is organized by defining the base unit of registration and categories. The results sought to answer the specific objectives: 1) to find out about the regulations on the student affirmative action policy at UESPI; 2) to analyse the administrative organizational structure following the implementation of the reservation system; 3) to identify strategies formulated in the regulatory instruments provided for the development of affirmative actions, which imply access and permanence of quota students; 4) elucidate the administrative structure of the composition of the higher education councils and its implications for establishing university policy for students; 5) describe the operational structure of affirmative action materialized in the dimensions of access and permanence; 6) present institutional evaluation and monitoring instruments that contribute to improving the institutionalization of the policy. The data from the Institutional Development Plans - PDI (2012-2016; 2017-2021) and the Institutional Strategic Plan - PEI (2014-2017), reveal that the legal and regulatory apparatus, which guide the practices in the processes of building the institutionalization of student affirmative actions are still embryonic. The understanding of the absence of records in the documents is that affirmative action for students is not an institutional priority, that the meritocracy bias is subtextual in what is not planned. This lack of planning has an impact of internal exclusion and delays the inclusion of black, indigenous, quilombola, disabled and other populations. In addition to the implications of maintaining the percentage of vacancy reservations incompatible with the black population of Piauí and the expansion of specific permanence policies for quota students. We conclude that the progress made in institutionalizing Affirmative Action for Students is taking place in a slow, trickle-down process.